(Con)Viver com HIV/AIDS: sentidos e significados para uma população atendida em um serviço de saúde no interior do estado de São Paulo - Ferreira, Carolina (Universidade Federal de São Carlos, 2025)
The first cases of AIDS emerged in 1981, but its cause—the HIV virus—was only identified years later. Being HIV-positive meant facing stigma, prejudice, and a death perceived as inevitable. More than just a disease, AIDS was morally condemned, associated with sexuality and so-called "risk behaviors," leading to symbolic losses and both physical and psychological suffering. With the advancement of antiretroviral therapy, HIV became a chronic condition, transforming its social representation and the ways of life of people living with the virus. This is an empirical, qualitative, and interpretive study that seeks to understand the changing meanings of living with HIV/AIDS today. It explores lifestyles, strategies for coping with chronic illness, the effects of diagnosis on mental health, and the lived experiences during the COVID-19 pandemic. Data collection took place in two stages: 1. A questionnaire including sociodemographic questions and the WHOQOL-HIV-Bref instrument (a quality of life indicator) and 2. Narrative interviews. A total of 42 people participated (n=42), mostly self-identified as white, cisgender men, heterosexual, with an average age of 44, completed secondary or higher education, and an individual income of one to two minimum wages. The WHOQOL-HIV-Bref results indicated an Intermediate or High quality of life, with the highest scores in the domain of “Spirituality/Religion and Personal Beliefs” and the lowest in “Level of Independence”. Based on the analysis of 12 interviews—with diagnoses between 2004 and 2019, undetectable viral loads, and Intermediate or High quality of life—the following thematic categories and corresponding meaning cores were identified: 1. Self-understanding and (co)living with HIV/AIDS today; 2. Diagnosis and clinical trajectory; 3. Coping strategies in the face of HIV/AIDS chronicity; 4. Subjectivities and HIV/AIDS; 5. HIV/AIDS and COVID-19 and 6. Health care and HIV/AIDS. Despite stigma and social inequalities, participants demonstrated a positive quality of life, particularly in subjective aspects such as spirituality and personal beliefs. The narratives revealed that, despite physical, emotional, and social challenges, living with HIV/AIDS involves coping strategies, reinterpretation, and meaning-making. The thematic categories enhance the understanding of these life trajectories, reinforcing the importance of integrated and humanized health care that goes beyond the biomedical model to include the psychosocial, emotional, and cultural dimensions of living with HIV.
(Living with) HIV/AIDS: meanings and significance for a population served by a health service in the interior of the state of São Paulo
Keywords: HIV/AIDS; Qualidade de vida; Representações sociais; Saúde mental; SUS; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL; 3. Saúde e Bem-Estar